Integrated chemical status of the Italian marine waters sensu Descriptor 8 of the Marine Strategy Framework Directive - Maggi, Chiara; Berducci, Maria Teresa; Di Lorenzo, Bianca; Lomiri, Serena; Venti, Francesco (Frontiers in Marine Science, 2022)
The European Marine Strategy Framework Directive (MSFD) required Member States to define the concept of Good Environmental Status (GES) of their marine waters in quantitative terms and to achieve it through the assessment of 11 descriptors by 2020. ISPRA (Italian Institute for Environmental Protection and Research), on behalf of the Ministry of the Environment, carried out the Initial Assessment (2012) and the evaluation of the first cycle of the MSFD (2012–2018) to understand the achievement of GES Descriptor 8 (“Contaminant concentrations are at levels that do not give rise to pollution effects”) and, now, in this second cycle of the MSFD (2018–2024), is conducting monitoring of D8C1 criterion elements (“Contaminant concentrations”). In this paper, the approach, integrating data on chemical contaminants (metals and polycyclic aromatic hydrocarbons and organochlorine compounds) in different matrices (water, sediment and biota), adopted by Italy since 2012 to study GES for the MSFD-D8C1 criterion in national marine water is described. This approach, based on the use of a dimensionless, zero-centered index, allows one to assess all regulatory contaminants as a whole. The improvements in the monitoring strategy and the GES evaluation between the Initial Assessment, the first cycle, and the beginning of the second cycle of the MSFD for the Adriatic Sea subregion are presented.